A checklist of Acari type specimens deposited in the Jalal Afshar Zoological Museum, Karaj, Iran - Saboori, Alireza; Shirvani, Zeinab (Zootaxa, 2021)
A checklist of the Acari type specimens deposited in the Jalal Afshar Zoological Museum (JAZM), Department of Plant Protection, Faculty of Agriculture, University of Tehran, Karaj, Iran is given. From a total of 451 type specimens (which comprises 166 valid species names) cited in the list, 164 are available and two are lost. Based on the comparison of these type specimens, the following taxonomic change is proposed in this paper: Erythraeus (Zaracarus) ueckermanni is considered as a valid species and is not a junior synonym of Erythraeus (Zaracarus) budapestensis.